Fabrication and properties of abradable sealing Al2024/hBN composites by hot-pressing sintering - ZHOU Lihua; FENG Qiang; HE Pengjiang; PAN Chaomei; LUO Hao; FU Naike; ZHU Jie; LI Zhi; SONG Xinqiang; ZENG Keli (Fenmo yejin jishu)
The abradable sealing Al2024/hBN composites were produced by hot-pressing sintering. The influence of ball milling time on the microstructure and mechanical properties was investigated. The results show that, the Al2024/hBN composites sintered by hot-pressing sintering have a relatively higher density and hardness, up to 2.52 g/cm3 and HR15Y 90, respectively. With the extension of ball milling time, the microstructure of the composites significantly changes from the spherical particle to the lamellar structure, the friction coefficient and volume wear rate reduce, reaching the minimum of 0.32 and 2.3×10−3mm3·m−1·N−1, respectively. The maximum bending force increases with the ball milling time, from 1.2 kN to 2.3 kN in the three-point bending test at room temperature.